Involvement in bullying and sleep disorders in Chinese early adolescents - Ding, Han; Cao, Leilei; Xu, Baoyu; Li, Yuan; Xie, Jinyu; Wang, Jun; Su, Puyu; Wang, Gengfu (Frontiers in Psychiatry, 2023)
Background School bullying may cause sleep disorders in early adolescents. Here, we determined the relationship between school bullying (considering all the features of bullying involvement) and sleep disorders, which are the common problems in Chinese early adolescents. Materials and methods We conducted a questionnaire survey among 5,724 middle school students from Xuancheng, Hefei, and Huaibei cities in Anhui province, China. The self-report questionnaires included the Olweus Bully/Victim Questionnaire and Pittsburgh Sleep Quality Index. We used latent class analysis to identify the potential subgroups of bullying behavior. Logistic regression analysis was used to investigate the association between school bullying and sleep disorders. Results Active participants in bullying interactions, including the bullies and victims, reported higher levels of sleep disorders compared with the non-active participants [Bully: physical (aOR = 2.62), verbal (aOR = 1.73), relational (aOR = 1.80), and cyber (aOR = 2.08); Victim: physical (aOR = 2.42), verbal (aOR = 2.59), relational (aOR = 2.61), and cyber (aOR = 2.81)]. A dose–response relationship was observed between the number of school bullying types and sleep disorders. In the context of bullying roles, bully-victims had the highest risk of reporting sleep disorders (aOR = 3.07, 95% CI: 2.55–3.69). We identified four potential categories of school bullying behaviors: low involvement in bullying, verbal and relational victims, medium bully-victims, and high bully-victims, and the highest frequency of sleep disorders was observed in the high bully-victims group (aOR = 4.12, 95% CI: 2.94–5.76). Conclusion Our findings indicate a positive correlation between bullying roles and sleep disorders in early adolescents. Therefore, targeted intervention for sleep disorders should include an evaluation of bullying experiences.